Perspective on Energetic and Thermal Atmospheric Photoelectrons - Peterson, W. K. (Frontiers in Astronomy and Space Sciences, 2021)
Atmospheric photoelectrons are central to the production of planetary ionospheres. They are created by photoionization of the neutral planetary atmosphere by solar EUV and soft X-ray irradiance. They provide the energy to heat the thermosphere. Thermalized photoelectrons permeate magnetospheres creating polarization electric fields and plasma waves as they interact with ions to maintain charge neutrality. Energetic photoelectrons (>1 eV) have a distinctive energy spectral shape as first revealed in data from the Atmosphere Explorer satellites. Energetic photoelectrons escaping the ionosphere follow local magnetic fields illuminating the planet’s magnetic topology. Current models using state-of-the-art EUV observations accurately capture their production and transport. However, in spite of 60 years of space research the electron thermalization processes occurring below 1 eV at low altitudes in planetary thermospheres are not understood quantitatively. Results from event analysis of data from the Mars Atmosphere and Volatile Evolution (MAVEN) mission are not consistent with current models of photoelectron thermalization. The lack of quantitative understanding reflects the complexity of the physics and the lack of a large data base of simultaneous neutral, ion, and electron densities and temperatures in lower planetary thermospheres.